Myoglobin and left ventricular ejection fraction as predictive markers for death in children with fulminant myocarditis - Tingting Xie; Xiaodong Zang; Yingying Xiong; Chaolei Yang; Fei Li; Dandan Wang; Yaqin Shu; Xuming Mo; Mingwu Chen; Mingwu Chen (Frontiers Media S.A., 2022)
BackgroundFulminant myocarditis (FM) is an inflammatory process of the myocardium and an important cause of cardiac dysfunction in children; it is characterized by rapid onset, acute progression, and high mortality. The study sought to describe the clinical characteristics and prognostic factors in children with FM.MethodsThe study population consists of 37 consecutive patients admitted from May 2014 to December 2021 with a diagnosis of FM. According to the prognosis of children with FM during hospitalization, they were divided into "survival" group (25 cases) and "death" group (12 cases). A multivariate logistic regression analysis was performed to identify the independent predictors of in-hospital mortality in the patients, and receiver operating characteristic (ROC) curve was used to explore the predictive value of related factors.ResultsThe 37 children with FM had an average age of 8.35 ± 4.36 years old. Twenty-five of the patients survived and 12 died. Twenty-five of the children were discharged from the hospital after a series of active rescue treatments such as nutritional myocardial drugs, high-dose intravenous immunoglobulin (IVIG), glucocorticoids (GCs), temporary pacemaker (TP), extracorporeal membrane oxygenation (ECMO), and continuous renal replacement therapy (CRRT).Twelve of the children were classified into the death group because the resuscitation failed. The levels of procalcitonin (PCT), creatine kinase (CK), and myoglobin (MYO) in the death group were all higher than in the survival group (all P < 0.05), and the left ventricular ejection fraction (LVEF) in the death group was significantly lower than in the survival group (P = 0.002). The binary logistic regression analysis revealed that MYO [OR:1.006; 95%CI:(1-1.012); P = 0.045] and LVEF [OR: 0.876; 95% CI: (0.785-0.978); P = 0.019] were independent predictors of FM. ROC curve analysis showed that the area under ROC curve (AUC) of MYO and LVEF was [AUC:0.957; 95%CI:0.897~1] and [AUC:0.836; 95%CI:0.668~1], and the area under the combined ROC curve for MYO + LVEF was significantly higher than that for MYO or LVEF alone (P < 0.05), indicating that the MYO + LVEF combined diagnosis had a higher predictive value for FM.ConclusionThe levels of MYO and LVEF can be markers for prognosis of FM and can effectively evaluate the disease severity. Their combination can improve forecast accuracy; thus, the detection of the above-mentioned indexes possesses a higher value for clinical applications.